Identifying Middle School Students’ Perceptions of STEAM Careers (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
The aim of this study was to identify the students' perceptions of STEAM careers. The effect of the STEAM intervention on students’ perceptions was evaluated using one group pretest - posttest experimental design with career questionnaire. The sampling of the study consists of 37 seventh grade middle school students. In the study, STEAM activities were used in the teaching of the Force and Energy unit. First of all, the students were asked about their career choices and their responses were evaluated quantitatively. There was statistically significant difference between the distributions of changes in the number of students choosing STEAM careers. Content analysis also was performed on the findings obtained from the questionnaire. As a result of the study, it was determined that the students increased the percentage of choosing careers in the STEAM career fields such as scientists and engineering. Looking at the interest of students in STEAM fields, one of the biggest changes was in the field of science. One of the important findings of the research was that after the implementation, the majority of the students thought that gender was not important in the success of STEAM career fields. The results of the research revealed that the STEAM education approach can be used a lot to evaluate and improve the academic career choices of middle school students.